The effective of service quality towards customer satisfaction at Majlis Amanah Rakyat Negeri Melaka / Mohd Ariff Noordin - Noordin, Mohd Ariff (Faculty of Business and Management, 2012)
This research study is about the effectiveness of service quality towards customer satisfaction at Majlis Amanah Rakyat Negeri Melaka (MARA Melaka). Dimension of service quality and customer satisfaction have been identified in order to investigate the relationship between dimensions of service quality towards customer satisfaction at MARA Melaka. The survey is conducted at MARA Melaka. The sample for this study is 100 respondents. The respondent will be selected by customers who come to the venue to get the services. Data obtained by using primary data. Respondent are required to answer the questionnaire that contain of element that potentially have relationship with the service quality and customer satisfaction. Data analyzed by using reliability test, frequency test, Pearson correlation analysis, and multi-regression analysis through SPSS program. The result shows that all the dimension in service quality which is tangible, reliability, responsiveness, assurance and empathy have significant relationship towards customer satisfaction. Furthermore, according to the finding result, there is high level of customer satisfaction at MARA Melaka. Moreover, the result also shows that rank contribution towards customer satisfaction is responsiveness, reliability and empathy.